Lithium nickel manganese oxide positive electrode material as well as preparation method and application thereof
Through fluidized bed technology, uniformly covering the surface of the positive electrode material of lithium-ion batteries is solved, and a more stable coating layer and higher battery circulation performance are achieved.
Patent Information
- Application Number
- CN202411935201.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The existing lithium-ion battery positive electrode material spinel LiNi0.5Mn1.5O4 (LNMO) has poor circulation performance, which makes it unable to meet the requirements in high-power applications, mainly because the surface contact with the electrolyte and the dissolution of metal ions affect the material's circulation and rate performance.
Fluidized bed technology is used to atomize organic matter such as titanate, aluminate and borate in an airflow, and mix it with the flowing positive electrode material to achieve uniform coating and quickly dry it in the fluidized bed to form a stable coating.
Through fluidized bed coating technology, uniform coating of the surface of the positive electrode material is achieved, cycling stability and safety of the material are improved, and the coating layer falls off and manganese dissolution is avoided, which significantly improves the cycling performance of the battery.
Smart Images

Figure CN119725476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium nickel manganese oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries have been widely used. As the demand for energy storage increases, lithium-ion batteries will eventually reach their density limit (about 400Whkg under ideal conditions). -1 ). Therefore, it is expected to develop batteries with high energy storage capacity and suitable for large-scale preparation. The cathode material is a decisive factor affecting the electrochemical performance and plays a leading role in the capacity, energy density and cycle performance of the battery. Therefore, the development of high energy density cathode materials is an important means to break the energy limitation of current lithium-ion batteries.
[0003] According to the working principle of lithium-ion batteries, the specification capacity and working voltage of the positive electrode material directly affect the energy density of lithium-ion batteries. Therefore, using high-capacity or high-working-voltage positive electrode materials to improve the energy density of lithium-ion batteries is an effective way to break through this limitation. 0.5 Mn 1.5 O4(LNMO) is low-cost and easy to manufacture industrially, and has an ultra-high discharge platform of about 4.7V (vs. Li / Li + ); LNMO also has a high energy density of about 650Wh / kgd, which is 1.63 times that of LiMn2O4 and 1.31 times that of LiFePO4. Therefore, high-voltage LNMO with a spinel structure is considered to be one of the most promising cathode materials for next-generation lithium-ion batteries in terms of high energy density, abundant raw materials, and large-scale production potential.
[0004] However, the cycle performance of bulk LNMO is poor, so it cannot fully meet the requirements of high power. The most critical problem of LNMO is the short cycle life caused by the rapid decline in capacity. This is mainly because when the high-voltage spinel LNMO is cycled under high-voltage conditions, its surface contacts the electrolyte and the metal ions are dissolved, which seriously affects the material's cycle and rate performance; and the highly active surface is easy to react with the electrolyte, which reduces the cycle performance and safety.
[0005] Existing technologies mostly use mechanical mixing of metal oxides and positive electrode materials, and then high-temperature sintering to achieve the coating effect. The metal oxide structure is stable and can effectively protect the material. However, for small-molecule metal oxide coating agents, the only way to reduce the impact of the electrolyte is to stack the surface and reach a certain thickness. This makes it difficult to obtain a uniform coating layer by mechanical mixing, and the coating layer is easily deformed during the cycle due to the deformation of the positive electrode material and the Li + De-embedding and shedding occur, which reduces the cycle performance and safety.
[0006] In addition to the above-mentioned solid phase coating method, the surface of the positive electrode material can also be coated by solution coprecipitation method, sol-gel method, etc. Although the conventional liquid phase coating method can uniformly coat a layer of metal oxide or organic matter on the surface of the positive electrode material to improve the cycle performance of the positive electrode material, the process is complicated and the processing cost is high. The atomic layer deposition (ALD) coating method can achieve uniform coating of a 1nm-2nm thick coating layer with excellent performance, but it has high requirements for equipment and raw materials, and the cost is also high, which is not conducive to industrial production.
[0007] Therefore, there is an urgent need to develop a simple, low-cost coating method that can achieve uniform coating effects while significantly improving the cycling performance of the material.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] The purpose of the present invention is to provide a lithium nickel manganese oxide positive electrode material and its preparation method and application, aiming to provide a simple and low-cost coating method, which can achieve a uniform coating effect and significantly improve the cycle performance of the material.
[0010] The present invention is achieved in that:
[0011] In a first aspect, the present invention provides a method for preparing a lithium nickel manganese oxide positive electrode material, comprising:
[0012] Providing lithium nickel manganese oxide positive electrode material to be modified;
[0013] Mixing a coating raw material and a solvent to obtain a coating material, spraying the coating material onto the surface of the lithium nickel manganese oxide positive electrode material to be modified in a fluidized bed, and drying in the fluidized bed;
[0014] The coating raw material is selected from at least one of titanate, aluminate and borate.
[0015] In an optional embodiment, the coating raw material is selected from at least two of titanate, aluminate and borate;
[0016] Preferably, the coating raw material includes titanate and aluminate, and the mass ratio of titanate to aluminate is 1:(0.5-1.5).
[0017] In an optional embodiment, the mass ratio of the total amount of the coating raw material to the solvent is 1:(8-10), and the mass ratio of the lithium nickel manganese oxide positive electrode material to be modified to the coating material is 1:(0.1-0.3);
[0018] Preferably, the solvent is water.
[0019] In an optional embodiment, the inlet temperature of the fluidized bed is controlled to be 100°C-140°C, the outlet temperature of the fluidized bed is 40°C-60°C, and the total residence time in the fluidized bed is 10min-200min;
[0020] The coating material is sprayed after the material to be modified lithium nickel manganese oxide positive electrode material enters the fluidized bed and reaches 40°C-80°C.
[0021] In an optional embodiment, the chemical formula of the lithium nickel manganese oxide positive electrode material to be modified is Li x Ni y Mn z O2, Li x Ni y Mn z O2, 0.5<x≤0.55, 0.2<y≤0.3, 0.7<z≤0.8, y+z=1.
[0022] In an optional embodiment, the preparation process of the modified lithium nickel manganese oxide positive electrode material includes: mixing and sintering a nickel cobalt hydroxide precursor, a lithium source and a dopant, controlling the sintering temperature to be 900° C.-1100° C., and holding time to be 8 h-12 h;
[0023] Preferably, after the heat preservation is completed, the powder is crushed and passed through a 300-500 mesh sieve.
[0024] In an optional embodiment, the doping element contained in the dopant is selected from at least one of Sr, Sb and Nb;
[0025] Preferably, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide and lithium oxide; and the molar ratio of the total amount of nickel and cobalt in the nickel-cobalt hydroxide precursor to the lithium content in the lithium source is controlled to be 1:(0.50-0.55).
[0026] In a second aspect, the present invention provides a lithium nickel manganese oxide positive electrode material prepared by any one of the preparation methods in the aforementioned embodiments.
[0027] In a third aspect, the present invention provides a positive electrode plate, comprising the lithium nickel manganese oxide positive electrode material of the aforementioned embodiment.
[0028] In a fourth aspect, the present invention provides a lithium battery comprising the positive electrode sheet of the aforementioned embodiment.
[0029] The present invention has the following beneficial effects: organic substances such as titanate, aluminate, borate, etc. are sprayed into the fluidized bed by air flow atomization spraying, and mixed with the positive electrode material in a flowing state, so as to realize the uniform coating of the positive electrode material by the coating raw material; after coating, it can be quickly dried in the fluidized bed, eliminating the step of drying separately, and effectively reducing the agglomeration and segregation of the coating agent on the positive electrode surface. The present invention uses fluidized bed coating to make the coating agent tightly and firmly coated on the surface of lithium nickel manganese oxide (LNMO) positive electrode material as a whole, avoiding the long-term immersion of the positive electrode in water or other solvents in the conventional liquid phase coating method; at the same time, the fluidized bed has its own crushing and dispersing effect, and has low requirements for the dispersibility of LNMO (even if the mono-alkane matrix has slight agglomeration, it does not affect the coating effect). The coating layer formed by this method is stable and not easy to fall off, and effectively prevents the direct contact between the surface of the LNMO positive electrode material and the electrolyte, effectively reducing manganese dissolution and improving the cyclic stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is a scanning electron microscope image of the positive electrode material obtained in Example 1;
[0032] Figure 2 The scanning electron microscope image of the positive electrode material obtained for Comparative Example 2;
[0033] Figure 3 This is a scanning electron microscope image of the positive electrode material obtained in Comparative Example 3. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0035] In view of the problem that the coating layer of the prior art LNMO positive electrode material is prone to falling off, which in turn affects the cycle performance and safety performance. The inventors considered using organic materials with good film-forming properties to assist in the coating, which can not only make the coating more uniform, but also the long-chain structure of the organic molecules can be better coated on the positive electrode material, and can also make the coating layer more stable during the cycle. In view of the problems of complex process and high processing cost of the traditional liquid phase coating method, the inventors optimized the coating process, which can significantly reduce the process cost while ensuring the coating effect.
[0036] The present invention provides a method for preparing a lithium nickel manganese oxide positive electrode material, the steps of which are as follows:
[0037] S1. Provide lithium nickel manganese oxide positive electrode material to be modified
[0038] The chemical formula of the lithium nickel manganese oxide positive electrode material to be modified is Li x Ni y Mn z O2, 0.5<x≤0.55, 0.2<y≤0.3, 0.7<z≤0.8, y+z=1. The modified lithium nickel manganese oxide positive electrode material can be a commercially available raw material or can be synthesized independently. Specifically, the value of x can be 0.51, 0.52, 0.53, 0.54, 0.55, etc.; the value of y can be 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.28, 0.30, etc.; the value of z can be 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.77, 0.78, 0.79, 0.80, etc.
[0039] In some embodiments, the preparation process of the modified lithium nickel manganese oxide positive electrode material includes: mixing and sintering a nickel cobalt hydroxide precursor, a lithium source and a dopant, controlling the sintering temperature to 900°C-1100°C, and holding time to 8h-12h. The sintered product is the LNMO positive electrode material, which can be used for subsequent coating processes.
[0040] Specifically, the sintering temperature may be 900°C, 950°C, 1000°C, 1050°C, 1100°C, etc., and the holding time may be 8h, 9h, 10h, 11h, 12h, etc. The heating rate is not limited, such as 1°C / min-5°C / min, and specifically 3°C / min.
[0041] In some embodiments, after the heat preservation is completed, the material is crushed and passed through a 300-mesh to 500-mesh sieve to obtain a positive electrode material with a particle size that meets the requirements for subsequent surface modification. The crushing method is not limited, for example, a common jaw crusher can be used.
[0042] The molar ratio of nickel to manganese in the nickel cobalt hydroxide precursor corresponds to the molar ratio of nickel to manganese in the chemical formula of the lithium nickel manganese oxide positive electrode material to be modified. The nickel cobalt hydroxide precursor can be purchased commercially or prepared by a conventional coprecipitation method.
[0043] In some embodiments, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide and lithium oxide, and the lithium source can be any one or more of the above; the molar ratio of the total amount of nickel and cobalt in the nickel cobalt hydroxide precursor to the lithium content in the lithium source is controlled to be 1:(0.50-0.55), such as 1:0.50, 1:0.51, 1:0.52, 1:0.55, 1:0.55, etc.
[0044] In some embodiments, the doping element contained in the dopant is selected from at least one of Sr, Sb and Nb, and the doping element may be any one or more of the above, and the dopant may be SrCO3, Sb2O3, Nb2O5, etc. The amount of the dopant can be adjusted according to the content of the doping element in the target modified lithium nickel manganese oxide positive electrode material.
[0045] S2, fluidized bed coating
[0046] The coating material is mixed with a solvent to obtain a coating material, the coating material is sprayed onto the surface of the lithium nickel manganese oxide positive electrode material to be modified in a fluidized bed, and dried in the fluidized bed; wherein the coating material is selected from at least one of titanate, aluminate and borate, and the coating material can be any one or more of the above.
[0047] It should be noted that organic substances such as titanate, aluminate, borate, etc. are sprayed into the fluidized bed by air flow atomization spraying, and mixed with the positive electrode material in a flowing state, so as to achieve uniform coating of the positive electrode material by the coating raw material; after coating, it can be quickly dried in the fluidized bed, eliminating the step of separate drying, and effectively reducing the agglomeration and segregation of the coating agent on the positive electrode surface.
[0048] In a preferred embodiment, the coating raw materials are selected from at least two of titanate, aluminate and borate. When the coating raw materials are any two of the above, the coating effect can be improved to a certain extent compared with one coating raw material, which is beneficial to the cycle stability of the positive electrode material.
[0049] In a more preferred embodiment, the coating raw material includes titanate and aluminate, and the mass ratio of titanate to aluminate is 1:(0.5-1.5). The use of titanate and aluminate as mixed coating raw materials for coating can further improve the electrochemical performance of the positive electrode material compared to other combinations. Specifically, the mass ratio of titanate to aluminate can be 1:0.5, 1:0.8, 1:1.0, 1:1.2, 1:1.5, etc.
[0050] Furthermore, the mass ratio of the total amount of the coating raw material to the solvent is 1:(8-10), such as 1:8, 1:8.5, 1:9, 1:9.5, 1:10, etc.; the mass ratio of the nickel manganese oxide positive electrode material to be modified and the coating material is 1:(0.1-0.3), such as 1:0.1, 1:0.2, 1:0.3, etc. The type of solvent is not limited, such as water. By further regulating the mass ratio of the total amount of the coating raw material to the solvent, and the mass ratio of the nickel manganese oxide positive electrode material to be modified and the coating material, the coating raw material can be coated more evenly to form a uniform and stable coating layer.
[0051] In the actual operation process, the nickel manganese oxide positive electrode material to be modified is placed in a fluidized bed, the inlet temperature of the fluidized bed is controlled to be 100°C-140°C, the outlet temperature of the fluidized bed is controlled to be 40°C-60°C, and the coating material is sprayed after the nickel manganese oxide positive electrode material to be modified enters the fluidized bed and reaches 40°C-80°C. The total residence time in the fluidized bed is 10min-200min (such as 10min, 30min, 50min, 80min, 100min, 130min, 150min, 180min, 200min, etc.). By precisely controlling the operating parameters of the fluidized bed, the coating material is better coated on the surface of the nickel manganese oxide positive electrode material to be modified, and then quickly dried to obtain a nickel manganese oxide positive electrode material with a stable coating layer.
[0052] Specifically, the inlet temperature of the fluidized bed can be 100°C, 110°C, 120°C, 130°C, 140°C, etc., and the outlet temperature of the fluidized bed can be 40°C, 45°C, 50°C, 55°C, 60°C, etc. The material temperature can be 40°C, 50°C, 60°C, 70°C, 80°C, etc. when spraying the coating material.
[0053] The embodiment of the present invention provides a lithium nickel manganese oxide positive electrode material, which is prepared by the preparation method provided by the embodiment of the present invention. The coating agent is tightly and firmly coated on the surface of the lithium nickel manganese oxide (LNMO) positive electrode material as a whole. The formed coating layer is stable and not easy to fall off and effectively prevents the direct contact between the surface of the LNMO positive electrode material and the electrolyte, effectively reduces manganese dissolution and improves the cycle stability of the material.
[0054] The embodiment of the present invention also provides a positive electrode plate, including the above-mentioned lithium nickel manganese oxide positive electrode material, and may also include a positive electrode current collector, a positive electrode active coating is formed on the positive electrode current collector, and the lithium nickel manganese oxide positive electrode material prepared in the embodiment of the present invention is dispersed in the positive electrode active coating. Since the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present invention has excellent cycle stability, the performance of the positive electrode plate is also improved accordingly.
[0055] An embodiment of the present invention further provides a lithium battery, including the above-mentioned positive electrode plate, and may also include a negative electrode plate, an electrolyte, a separator, etc., to form a complete lithium battery.
[0056] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0057] Example 1
[0058] This embodiment provides a method for preparing a lithium nickel manganese oxide positive electrode material, the steps are as follows:
[0059] (1) Preparation of LiNiMnO4 cathode material to be modified
[0060] Provide Ni 0.25 Mn 0.75 The (OH)2 precursor was purchased from Yibin Guangyuan Lithium Battery Company with model number Y1NM20106.
[0061] Ni 0.25 Mn 0.75 1 kg of (OH)2 precursor, 207 g of lithium carbonate, and dopants SrCO3 5 g, Sb2O3 5 g, and Nb2O5 5 g were mixed evenly and heated to 980 °C at a heating rate of 3 °C / min and kept for 10 h. After calcination, the high-voltage spinel LNMO positive electrode material Li 0.5 Ni 0.25 Mn 0.75 O2, after crushing, pass through 400 mesh sieve for later use.
[0062] (2) Fluidized bed coating
[0063] 10g of titanate and 10g of aluminate were dissolved in 180g of water to prepare a coating material, and the coating material was sprayed onto the surface of a sintered material (1kg) by a rolling fluidized bed (purchased from a company) in a wet coating manner, and dried in the fluidized bed until the moisture content was less than 300ppm, to obtain a lithium nickel manganese oxide positive electrode material co-coated with a titanate / aluminate. The inlet temperature of the fluidized bed was controlled to be 120°C, the outlet temperature of the fluidized bed was 50°C, and the coating material was sprayed after the lithium nickel manganese oxide positive electrode material to be modified entered the fluidized bed and reached 60°C, and the total residence time in the fluidized bed was 40min.
[0064] Example 2
[0065] The only difference between this embodiment and embodiment 1 is that the coating raw materials in step (2) are 30 g of titanate and 30 g of aluminate, and the amount of water remains unchanged.
[0066] Example 3
[0067] The only difference between this embodiment and embodiment 1 is that the coating raw materials in step (2) are 10 g of borate and 10 g of aluminate, and the amount of water remains unchanged.
[0068] Example 4
[0069] The only difference between this embodiment and embodiment 1 is that in step (2), 10 g of titanate and 10 g of aluminate are replaced by 20 g of titanate.
[0070] Example 5
[0071] The only difference between this embodiment and embodiment 1 is that in step (2), 10 g of titanate and 10 g of aluminate are replaced by 20 g of aluminate.
[0072] Example 6
[0073] The only difference between this embodiment and embodiment 1 is that the amount of water used in step (2) is 120 g.
[0074] Example 7
[0075] The only difference between this embodiment and embodiment 1 is that the amount of water used in step (2) is 240 g.
[0076] Example 8
[0077] The only difference between this embodiment and embodiment 1 is that the amount of burning material used in step (2) is 4 kg.
[0078] Example 9
[0079] The only difference between this embodiment and embodiment 1 is that the amount of burning material used in step (2) is 0.4 kg.
[0080] Comparative Example 1
[0081] The only difference between this embodiment and embodiment 1 is that the coating raw materials are 100 g of borate and 100 g of aluminate, and the amount of water remains unchanged.
[0082] Comparative Example 2
[0083] The difference between this embodiment and embodiment 1 is that step (2) uses solution coprecipitation method for coating, and the concentration of coating agent solution is lower. The specific steps are as follows:
[0084] 10 g of titanate and 10 g of aluminate were dissolved in 980 g of water to prepare coating solution A, high-voltage spinel LNMO positive electrode material was added to solution A and stirred for 1 hour, and the finished product was obtained after filtration and drying.
[0085] Comparative Example 3
[0086] The only difference between this embodiment and embodiment 1 is that the preparation process of the coating material in step (2) is as follows: 10 g of aluminum oxide, 10 g of titanium oxide and 180 g of water are mixed to obtain an inorganic oxide suspension.
[0087] Comparative Example 4
[0088] The difference between this embodiment and embodiment 1 is that step (2) uses a solution co-precipitation method for coating. The specific steps are as follows:
[0089] 10 g of titanate and 10 g of aluminate were dissolved in 180 g of water to prepare coating solution A, high-voltage spinel LNMO positive electrode material was added to solution A and stirred for 1 hour, and the finished product was obtained after filtration and drying.
[0090] Test example
[0091] (1) Taking Example 1 and Comparative Examples 2 and 3 as examples, the obtained ternary positive electrode materials were observed by scanning electron microscopy. The SEM images are as follows: Figure 1 , Figure 2 and Figure 3 shown.
[0092] Depend on Figures 1 to 3 It can be seen that the use of a fluidized bed to assist in the coating of organic metal compounds such as titanate esters and aluminum titanate allows the overall complex to be tightly and firmly coated on the surface of the LNMO positive electrode material, which can slow down the agglomeration of the coating layer during traditional wet coating methods and inorganic coating, and can make the coating layer more uniform and more stable.
[0093] (2) The ternary positive electrode materials obtained in the examples and comparative examples were used to make 2025-type button batteries and conduct electrochemical performance tests. The preparation and testing methods are as follows:
[0094] Ternary positive electrode: carbon black: PVDF = 90:5:5; negative electrode: metal lithium; electrolyte: Xinzhoubang (M10). The charge and discharge voltage range is 3.5-4.95V. The battery is mainly charged and discharged once at different rates of 0.1C, 0.2C, 0.5C, and 1C. Finally, the 1C capacity and cycle performance are tested at room temperature. The results are shown in Table 1.
[0095] Table 1 Capacity and cycle performance test results
[0096]
[0097]
[0098] It can be seen from Table 1 that the ternary positive electrode material obtained in the embodiment is more conducive to improving the battery's charge capacity and cycle retention rate than the ternary positive electrode material obtained in the comparative example, and the comprehensive effect of Example 1 is the best.
[0099] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium nickel manganese oxide positive electrode material, characterized in that: include: Providing lithium nickel manganese oxide positive electrode material to be modified; Mixing a coating raw material and a solvent to obtain a coating material, spraying the coating material onto the surface of the lithium nickel manganese oxide positive electrode material to be modified in a fluidized bed, and drying in the fluidized bed; Wherein, the coating raw material is selected from at least one of titanate, aluminate and borate.
2. The preparation method according to claim 1, characterized in that: The coating raw materials are selected from at least two of titanate, aluminate and borate; Preferably, the coating raw material comprises titanate and aluminate, and the mass ratio of titanate to aluminate is 1:(0.5-1.5).
3. The preparation method according to claim 1, characterized in that: The mass ratio of the total amount of the coating raw material to the solvent is 1:(8-10), and the mass ratio of the lithium nickel manganese oxide positive electrode material to be modified to the coating material is 1:(0.1-0.3); Preferably, the solvent is water.
4. The preparation method according to claim 1, characterized in that: The inlet temperature of the fluidized bed is controlled to be 100°C-140°C, the outlet temperature of the fluidized bed is controlled to be 40°C-60°C, and the total residence time in the fluidized bed is controlled to be 10min-200min; The coating material is sprayed after the temperature of the lithium nickel manganese oxide positive electrode material to be modified entering the fluidized bed reaches 40° C.-80° C.
5. The preparation method according to claim 1, characterized in that: The chemical formula of the lithium nickel manganese oxide positive electrode material to be modified is Li x Ni y Mn z O2, 0.5<x≤0.55, 0.2<y≤0.3, 0.7<z≤0.8, y+z=1.
6. The preparation method according to claim 5, characterized in that: The preparation process of the modified lithium nickel manganese oxide positive electrode material comprises: mixing and sintering a nickel cobalt hydroxide precursor, a lithium source and a dopant, controlling the sintering temperature to be 900° C.-1100° C., and holding the temperature for 8 h-12 h; Preferably, after the heat preservation is completed, the powder is crushed and passed through a 300-500 mesh sieve.
7. The preparation method according to claim 6, characterized in that: The doping element contained in the dopant is selected from at least one of Sr, Sb and Nb; Preferably, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide and lithium oxide; and the molar ratio of the total amount of nickel and cobalt in the nickel-cobalt hydroxide precursor to the lithium content in the lithium source is controlled to be 1:(0.50-0.55).
8. A lithium nickel manganese oxide positive electrode material, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 7.
9. A positive electrode sheet, characterized in that: Including the lithium nickel manganese oxide positive electrode material as described in claim 8.
10. A lithium battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Positive pole material for lithium ion battery and preparation method of positive pole material
CN103247797A
Coated modified electrode material and preparation method thereof
CN109585797A
Coating method of nickel cobalt lithium manganate ternary positive electrode material
CN111769273A
Multi-element coated core-shell structure lithium ion positive electrode material and preparation method thereof
CN113716549A
Process for making an at least partially coated electrode active material
WO2019179815A1
Cited By
Modified lithium nickel manganese oxide positive electrode material, preparation method thereof and battery
CN119725475A
Modified lithium nickel manganese oxide cathode material, preparation method thereof and battery
CN119725475B
Preparation method of high-voltage single-crystal spinel lithium nickel manganese oxide positive electrode material
CN121407226A